(3HPd GdeGYhf aj aVd GdWGYhfs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3CeG HYO abO JcQQ SDGd GdENhGf ai LejY GdGNHGQ GdhGQOI ai GdWGYhf eY TQM ZQjHgG hJjSjQ eYGfjgG Ydi GdCagGe aCLHJ QZHJge ai Pdc hQJHJg Ydi NeSI CHhGH s
(3BNQgG (B:s
(3bdJ hMci di ef CKb Hg Gfg TGgO ai LGeY YeQh Hf GdYGU fMh Pdc hbQCJ ai JPcQI GdbGVi UdGM GdOjf Ndjd Hf CjHc GdUaOi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B237s
Keywords: (3GdMOjK h GdeUWdMs